The Impact of Payments to Foreign Recipients in the Economic Policy of the State - Storz, Pawel (Warsaw Forum of Economic Sociology, 2020)
From the point of view of the deepening globalization processes in the world economy, developing the sphere of foreign trade (including primarily international trade in services) is of key importance. It is worth noting that as part of international trade, the payment for services to foreign recipients determine the functioning of the sphere of foreign trade. The method of taxation of the analyzed payments has an wide impact on shaping the economic policy of the state. The aim of this article is to present the taxation of payments to foreign recipients as one of the tools in shaping the economic policy of the state based on the example of the presented contrast of the Polish economy and the highly developed economies of Hong Kong and Singapore. The methodology used in this paper is critical literature analysis. The obtained research results indicate the need for the fiscal authorities to pay more attention in practice to the methods and ways of the taxation of payments to foreign recipients, as the main factor in the development of the foreign trade sphere. The conclusions presented in this paper show a wide range of impact of the methods of taxation of payments to foreign recipients on the development of the economic policy of the state, with particular emphasis on the area of foreign trade. The author‘s contribution to the development of the discipline, is an indication of new and practical actions for state authorities in influencing the development of the sphere of foreign trade and economic policy of the state based on the example of the presented contrast of the Polish economy and the highly developed economies of Hong Kong and Singapore. The article aims at describing the theoretical inspirations and research traditions behind the evolution of industrial relations in Poland. The account of global theoretical debate since the emerging of the field in the first half of the 20th century is delivered, followed by the overview of academic debates and research concerning the field since the times of state socialism (1945–1989) until the present day in Poland. In the conclusion, it is stated that in theoretical terms the field of industrial relations has remained underdeveloped.